Alzheimer's disease pathology and shunt surgery outcome in normal pressure hydrocephalus. - Sevil Yasar; Ignacio Jusue-Torres; Jennifer Lu; Jamie Robison; Mira A Patel; Barbara Crain; Kathryn A Carson; Jamie Hoffberger; Sachin Batra; Eric Sankey; Abhay Moghekar; Daniele Rigamonti (PLoS ONE)
We aimed to determine whether presence of AD neuropathology predicted cognitive, gait and balance measures in patients with idiopathic normal pressure hydrocephalus (iNPH) after shunt surgery. This is a prospective study of gait and balance measured by Timed Up and Go (TUG) and Tinetti tests, and cognitive function measured by Mini Mental Status Exam (MMSE), before and after shunt surgery in participants 65 years and older with iNPH at the Johns Hopkins University. Random effects models were used and adjusted for confounders. 88 participants were included in the analysis with a median (IQR) time of 104 (57-213) days between surgery and follow-up. 23 (25%) participants had neuritic plaques present (NP+) and were significantly older [76.4 (6.0) years], but were otherwise similar in all demographics and outcome measures, when compared to the group without neuritic plaques (NP-). NP- and NP+ participants equally improved on measures of TUG (β = -3.27, 95% CI -6.24, -0.30, p = 0.03; β = -2.37, 95% CI -3.90, -0.86, p = 0.02, respectively), Tinetti-total (β = 1.95, 95% CI 1.11, 2.78, p<0.001; β = 1.72, 95% CI 0.90, 2.53, p<0.001, respectively), -balance (β = 0.81, 95% CI 0.23, 1.38, p = 0.006; β = 0.87, 95% CI 0.40, 1.34, p<0.001, respectively) and -gait (β = 1.03, 95% CI 0.61, 1.45, p<0.001; β = 0.84, 95% CI 0.16, 1.53, p = 0.02, respectively), while neither NP- nor NP+ showed significant improvement on MMSE (β = 0.10, 95% CI -0.27, 0.46, p = 0.61, β = 0.41, 95% CI -0.27, 1.09, p = 0.24, respectively). In summary, 26% of participants with iNPH had coexisting AD pathology, which does not significantly influence the clinical response to shunt surgery.